1984
DOI: 10.1093/carcin/5.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Colcemid-induced neoplastic transformation and aneuploidy in Syrian hamster embryo cells

Abstract: Treatment of Syrian hamster embryo cells in culture with 0.01-0.1 micrograms/ml of colcemid for 48 h resulted in morphological and neoplastic transformation of the cells. Cell transformation was observed with doses which were non-cytotoxic and did not cause mitotic inhibition of the cells. Higher dose of colcemid (greater than 0.1 microgram/ml) resulted in mitotic inhibition of the cells and a significant loss of colony forming ability, but no increase in the frequency of morphological transformation. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…It has been shown that colcemid causes aneuploidy in CHE cells (79) and also transforms Syrian Hamster cells in culture (81). Following these procedures, we have treated CHE cells with 0.02 g͞ml colcemid thrice for 2 days in consecutive transfers.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that colcemid causes aneuploidy in CHE cells (79) and also transforms Syrian Hamster cells in culture (81). Following these procedures, we have treated CHE cells with 0.02 g͞ml colcemid thrice for 2 days in consecutive transfers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, classical transformation experiments have suggested that a spindle-disrupting drug, colcemid, is carcinogenic due to changes in the chromosome number (Tsutsui et al, 1984). We therefore examined the effect of spindle-disorganizing drugs on BALB/c 3T3 A31-1-1 cells, which are susceptible to physical and chemical carcinogens (Kakunaga and Crow, 1980), as well as various oncogenes (Tatsuka et al, 1996).…”
mentioning
confidence: 99%
“…However, both of them induce not only perturbations of chromosome number but also carcinogenicity after a long period of cultivation (Tsutsui et al, 1984;Ota et al, 2002). In classical transformation experiments, the long-term culture of rodent cells is generally known to induce spontaneous transformation, a process caused by activation of certain endogenous retroviral or cellular oncogenes.…”
mentioning
confidence: 99%
“…Pfeiffer et al (1996Pfeiffer et al ( , 1997 reported aneuploidogenic properties of BP-A, i.e., inhibition of microtubule (MT) assembly in intact cells and under cell-free conditions and induction of both metaphase arrest and micronuclei-containing chromatids or whole chromosomes in cultured Chinese hamster V79 cells. Chemical compounds inducing numerical chromosomal changes, such as Colcemid and vincristine sulfate, have been demonstrated to cause morphological and neoplastic transformations of cultured Syrian hamster embryo (SHE) cells (Tsutsui et al, 1984(Tsutsui et al, , 1986. 17␤-Estradiol (E 2 ) and the synthetic estrogen diethylstilbestrol (DES) also induce numerical chromosomal changes (i.e., aneuploidy) and cellular transformation in SHE cells (Tsutsui et al, 1983(Tsutsui et al, , 1987(Tsutsui et al, , 1997.…”
mentioning
confidence: 99%